Discalculia: uma análise bibliográfica - CUIMAR, Misael Pantoja (2019)
This work seeks to arouse the interest of knowing the dyscalculia and emphasizes in it its main bibliographical references, and tries to become the same known by the professionals of education and especially by teachers of Mathematics and Pedagogy. Considering that the students' various difficulties present themselves in different ways regarding learning in relation to their mathematical skills to develop possible calculations, where dyscalculia has a large portion that hinders such skills, therefore, there was a need to perform such Therefore, dyscalculia affects children's cognition, preventing them from succeeding at school. It is precisely this fact that has given due attention to this topic of such importance as it is relevant for a future change in the teaching and learning of mathematics. Given the above, we seek to better understand the subject, presenting a union of pedagogical and psychopedagogical interventions together with the aid of technological tools, enabling the perception of the emergence of dyscalculia and its symptoms for a better understanding of this learning disorder, as it affects negatively the student's school life, a fact that draws the attention of many professionals in the world education.